Automatic assembly design project 1968/9 : Report of economic planning committee - Jones, P. V.; Pettitt, M. E.; Kaloo, U. (College of Aeronautics, 1969)
Investigations into automatic assembly systems have been carried out. The conclusions show the major features to be considered by a company operating the machine to assemble the contact block with regard to machine output and financial aspects. The machine system has been shown to be economically viable for use under suitable conditions, but the contact block is considered to be unsuitable for automatic assembly. Data for machine specification, reliability and maintenance has been provided.